Vägen till Metropolis: Svenska gesällvandringar vid sekelskiftet 1900 - Ericsson, Tom (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2008)
From the Middle Ages to the abolition of the guilds in the nineteenth century travelling was central within the European handicrafts. Each person who would become a master artisan had during his formation to learn his profession from other master artisans. Therefore, apprentices and journeymen worked for shorter or longer periods in the workshops of older master artisans either at home or in another European country. This article shows that the traditional educational pattern within the handicrafts continued in Sweden long after the abolition of the guilds and the introduction of the free trade, and many Swedish craftsmen migrated to the European capitals where they could gain experiences from foreign experts, which they could bring back and introduce in Sweden. Compared to the mass emigration to United States, which took place at the same time, this is an example of what the American historian and sociologist Charles Tilly has called "career migration". The Swedish artisans wanted to improve their skill and this is the reason why they migrated.